Bimetallic-doped Zeolitic imidazole framework-derived Cobalt-Nitrogen-Carbon supported on reduced graphene oxide enabling efficient microwave absorption; Journal of the Taiwan Institute of Chemical Engineers; Vol. 134 - Chen Qi; Su Xiaogang; Liu Xing; Wang Jichao; Song Rongguo; He Daping; Chaemchuen Somboon; Verpoort F. V. K. Frensis Valter Kornelius (2022, 2022)
Title screen